Paradigmatic principles of social geographic knowledge - Шуканов, Павло (Human Geography Journal, 2016)
The article analyzes the main stages in the development of geographical knowledge. The author accents attention on the value of single paradigm of time in development of social geographical knowledge.. The problem of desacralization  of scientific knowledge is taken into account in the article, as an important factor of system crisis is in geography. The author highlights the value of tradition, modernization and transformation of information in scientific knowledge of nature and society. The article proposes to use metaphysical principles as a basis for improvement and use of the sacral-geographical paradigm.